0142 Mental health in childhood as risk indicator of labour market participation in young adulthood. A prospective birth cohort study. (23rd June 2014) - Lund, Thomas; Hviid Andersen, Johan; Labriola, Merete
Abstract : Objectives: The aim of this study was to investigate if mental health status in childhood determined future labour market participation, and to identify if effects varied across gender and social strata. Method: Of a cohort of 3681 born in 1989 in the county of Ringkjoebing, Denmark, 3058 (83%) completed a questionnaire in 2004. They were followed in a register on social benefits for 12 months in 2010–2011. Logistic regression was used to investigate associations between mental health in childhood measured with The Centre for Epidemiological Studies Depression Scale for Children (CES-DC) and future labour market participation, taking into account effects of socio-economic position, school performance, educational plans and vocational expectations. Results: A total of 17.1% (19.9% males, 14.4% females) received social benefits for at least 4 weeks during follow-up. Girls scored significantly lower on mental health than did boys. Labour market participation in early adulthood decreased with poor mental health in childhood, but only for boys: Boys with a baseline CES-DC score in the lowest quartile had a 70 % excess risk of low labour market participation after 7 years of follow-up. The association persisted when taking into account socio-economic position, but became borderline significant when adjusting for school performance, educational plans and vocational expectations. The negative effect was even across social strata. Conclusions: Despite girls scoring significantly lower on mental health than do boys, the effects on future labour market participation was only present among boys. The effect of poor mental health on future labour market participation did not vary across social strata.